Plasma irisin levels progressively increase in response to increasing exercise workloads in young, healthy, active subjects - Daskalopoulou, Stella S; Cooke, Alexandra B; Gomez, Yessica-Haydee; Mutter, Andrew F; Filippaios, Andreas; Mesfum, Ertirea T; Mantzoros, Christos S (European journal of endocrinology, 2014)
Irisin, a recently discovered myokine, has been shown to induce browning of white adipose tissue, enhancing energy expenditure and mediating some of the beneficial effects of exercise. We aimed to estimate the time frame of changes in irisin levels after acute exercise and the effect of different exercise workloads and intensities on circulating irisin levels immediately post-exercise. In a pilot study, four healthy subjects (22.5±1.7 years) underwent maximal workload exercise (maximal oxygen consumption, VO2 max) and blood was drawn at prespecified intervals to define the time frame of pre- and post-exercise irisin changes over a 24-h period. In the main study, 35 healthy, non-smoking (23.0±3.3 years) men and women (n=20/15) underwent three exercise protocols ≥48-h apart, in random order: i) maximal workload (VO2 max); ii) relative workload (70% of VO2 max/10 min); and iii) absolute workload (75 W/10 min). Blood was drawn immediately pre-exercise and 3 min post-exercise. In the pilot study, irisin levels increased by 35% 3 min post-exercise, then dropped and remained relatively constant. In the main study, irisin levels post-exercise were significantly higher than those of pre-exercise after all workloads (all, P<0.001). Post-to-pre-exercise differences in irisin levels were significantly different between workloads (P=0.001), with the greatest increase by 34% following maximal workload (P=0.004 vs relative and absolute). Circulating irisin levels were acutely elevated in response to exercise, with a greater increase after maximal workload. These findings suggest that irisin release could be a function of muscle energy demand. Future studies need to determine the underlying mechanisms of irisin release and explore irisin's therapeutic potential.